Victims of trauma by external causes in the city of Uberaba-mg - Ribeiro Chavaglia, Suzel Regina; Scarelli Amaral, Eliana Maria; Barbosa, Maria Helena; Borges Bittar, Daniela; Miranda Ferreira, Paula (O Mundo da Saúde, 2008)
This is a retrospective study, with a quantitative approach aiming to analyze the occurrence of traumas by external causes in the city of Uberaba-MG. Data were collected on the database of the Rescue Service of the Firemen Corporation of the City of Uberaba- MG, from January 1, 2004 to December 31, 2004. It was verified that, from the 3796 rescue operations done in 2004, 2331 (61.40%) involved victims of trauma by external causes. Of these, 27.00% (642) corresponded to motorcycle accidents, 19.00% (450) to falls, 15.00% (339) to bicycle accidents, 8.00% (179) to running overs and 6.00% (139) to car accidents and physical aggression by cutting weapons or guns. Regarding sex, most victims, 2677 (98.70%) were male and only 35 (1.30%) were female. Most accidents happened in Saturdays (18.00%), and some in Sundays (16.00%) and Fridays (14.00%), being December the month of a greater incidence - 168 cases (10.00%). Data allowed tracing the profile of the victims of trauma in the city of Uberaba-MG and, thus, to subsidize the elaboration of programs intended for the risk population with a focus in preventive actions against the occurrence of these traumas. One expects, from the implementation of these programs, to reduce the incidence of these accidents in the city of Uberaba-MG.